Peningkatan Keterampilan 4C Siswa Melalui Pengembangan Kompetensi Guru Dalam Kurikulum Merdeka - Daga, Agustinus Tanggu; Kaleka, Lasarus Bulu; Bili, Fransiskus Ghunu (Graduate School of Universitas Negeri Malang, 2024)
Teachers are figures that can influence student learning outcomes. A serious problem faced by elementary school students in Tambolaka CitySouthwest Sumbais the low 21st century skills of students. One of the smart efforts to improve students' 21st century skills is to improve teacher competence. The purpose of this study is to describethe relationshipof teacher competence with improving 4C skills of elementary school students. The method used was a survey with a questionnaire instrument. Data analysis used description analysis and correlation analysis. This study found that (1) teacher competence and student skills are moderate, (2) there is a significant relationship between teacher competence and students' critical thinking, collaboration, communication, creativity skills. What is different from this study is that teacher competence correlates higher with students' collaboration skills than with other 4C skills. Based on the results of this studythento improve students' 4C skills in Tambolaka Municipal District, teachers must continue to improve the 4 competencies through relevant education and training.Guru merupakan figur yang dapat mempengaruhi hasil belajar siswa. Permasalahan serius yang dihadapi oleh siswa Sekolah Dasar di Kota Tambolaka Sumba Barat Daya adalah rendahnya keterampilan abad 21 siswa. Salah satu upaya cerdas untuk meningkatkan keterampilan abad 21 siswa adalah meningkatkan kompetensi guru. Tujuan penelitian ini adalah untuk mendeskripsikan hubungan kompetensi guru dengan meningkatkan keterampilan 4C siswa Sekolah Dasar. Metode yang digunakan adalah survei dengan instrumen angket. Analisis data menggunakan analisis deskripsi dan analisis korelasi. Penelitian ini menemukan bahwa (1) kompetensi guru dan keterampilan siswa tergolong sedang, (2) terdapat hubungan yang signifikan kompetensi guru dengan keterampilan berpikir kritis, kolaborasi, komunikasi, kreativitas siswa. Hal yang berbeda dengan penelitian ini adalah kompetensi guru berkorelasi lebih tinggi dengan keterampilan kolaborasi siswa dibandingkan dengan keterampilan 4C lainnya. Berdasarkan hasil penelitian ini maka untuk meningkatkan keterampilan 4C siswa di Kabupaten Kota Tambolaka, guru harus terus meningkatkan 4 kompetensi tersebut melalui pendidikan dan pelatihan yang relevan.